Post-Traumatic Torticollis Due to Odontoid Fracture in a Patient With Diffuse Idiopathic Skeletal Hyperostosis: A Case Report. Issue 36 (September 2015) - Tsuji, Shotaro; Inoue, Shinichi; Tachibana, Toshiya; Maruo, Keishi; Arizumi, Fumihiro; Yoshiya, Shinichi
Abstract : Abstract: Descriptive case report. To report a rare case of post-traumatic torticollis by odontoid fracture in a patient with diffuse idiopathic skeletal hyperostosis (DISH). Cervical fractures in DISH can result from minor trauma, and a delay in presentation often prevents their timely diagnosis. Cervical fractures in patients with spinal DISH usually occur in extension injuries, and almost always occur in the lower cervical spine. Reports of odontoid fractures with torticollis in patients with spinal DISH are rare. A 73-year-old man with DISH presented with severe neck pain and a cervical deformity presenting as torticollis without neurological deficits. He gave a history of a fall while riding a bicycle at a low speed 3 months ago. X-ray showed torticollis in the right side, and computed tomography (CT) showed a type-II odontoid fracture and subluxation at the C1-2 level. We performed a staged treatment because this patient had severe neck pain associated with a chronic course. Initially, the fracture dislocation was reduced under general anesthesia and was stabilized with a halo vest. We then performed posterior occipitocervical in situ fusion after confirming the correction of the cervical deformity by CT. The patient showed significant amelioration of neck symptoms postoperatively, and bony fusion was achieved 1 year after surgery. For post-traumatic torticollis due to an odontoid fracture, plain CT is useful for diagnosis and posterior occipitocervical in situ fusion following correction and immobilization with a halo vest is a safe and an effective treatment.